2016
DOI: 10.3126/njh.v13i2.15561
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Valvular Involvement in Rheumatic Heart Disease Patients in a Tertiary Care Hospital of Western Nepal

Abstract: Background and Amis: Rheumatic Heart Disease (RHD) is among the commonest diseases of young adults in low-income countries like Nepal. Mitral and aortic valves are more commonly affected than others in RHD. Echocardiography is simple and cost effective tool to identify the patterns of valvular involvement that helps in diagnosis and determines the timing of surgery. This study aimed at determining the pattern of RHD in patients who underwent Echocardiography in a tertiary care hospital of western Nepal.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 7 publications
2
11
0
Order By: Relevance
“…RHD was most common in age group 21-40 years and females were more commonly involved than males. These finding correlated with observations of Manjunath et al and Kafle et al 18,19 Manjunath et al observed that majority of patients of valvular heart disease (64.3%) were due to RHD. 18 The pattern of association of valve involvement in RHD was mitral followed by aortic, tricuspid, and pulmonary.…”
Section: Discussionsupporting
confidence: 91%
“…RHD was most common in age group 21-40 years and females were more commonly involved than males. These finding correlated with observations of Manjunath et al and Kafle et al 18,19 Manjunath et al observed that majority of patients of valvular heart disease (64.3%) were due to RHD. 18 The pattern of association of valve involvement in RHD was mitral followed by aortic, tricuspid, and pulmonary.…”
Section: Discussionsupporting
confidence: 91%
“…Similar reports were shown in studies done in Nepal where MS was the most common valvular heart lesion in RHD. 9 , 10 Surgical pathology data have demonstrated rheumatic involvement in over 99 percent of excised stenotic valves, 20 , 21 which is consistent with the findings of a vast necropsy series (100%). 22 Congenital MS, which occurs in around 1% of cases, is uncommon in adults since the median age at death is only 2 months.…”
Section: Discussionsupporting
confidence: 57%
“… 6 , 8 Similar findings were found in a study done in Nepal. 9 , 10 Consistent patterns of valve disease distribution reveal that older age is an independent determinant of all types of valve disease that occur often in the elderly, supporting the assumption that the burden of valve illness rises with age.…”
Section: Discussionmentioning
confidence: 73%
“…Similarly, in the study of Kafle RC et al 50% of the patients belonged to age group 21-40 years. 12 Geographical distribution of RHD In this study majority of the admitted patients were from Central Development Region followed by Western and Eastern Development Region The main reason for this might be easy availability of health services and transportation facilities, awareness about the disease among the people and high population density. Least number of patients were admitted from Far Western Region; however, this does not mean that the prevalence of RHD is less in this region.…”
Section: Discussionmentioning
confidence: 99%